2020
DOI: 10.1038/s41598-020-76644-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inflammation markers for predicting oncological outcomes after surgical resection of non-small-cell lung cancer: a validated analysis of 2,066 patients

Abstract: Clinical and pathological predictors have proved to be insufficient in identifying high-risk patients who develop cancer recurrence after tumour resection. We aimed to compare the prognostic ability of various inflammation markers in patients undergoing surgical resection of lung cancer. We consecutively included 2,066 patients with stage I–III non-small-cell lung cancer undergoing surgical resection at the center between 2005 and 2015. We evaluated prognostic nutritional index, neutrophil-to-lymphocyte ratio,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…G‐CSF and GM‐CSF are cytokines that stimulate bone marrow to produce myeloid cells, such as monocytes and neutrophils. Preliminary studies reported that high serum levels of G‐CSF or GM‐CSF may be useful for lung cancer diagnosis 20–22 . In the present study, increases in both myeloid cells and myeloid cell‐specific CSFs were detected using several types of cell subsets and CSFs.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…G‐CSF and GM‐CSF are cytokines that stimulate bone marrow to produce myeloid cells, such as monocytes and neutrophils. Preliminary studies reported that high serum levels of G‐CSF or GM‐CSF may be useful for lung cancer diagnosis 20–22 . In the present study, increases in both myeloid cells and myeloid cell‐specific CSFs were detected using several types of cell subsets and CSFs.…”
Section: Discussionsupporting
confidence: 58%
“…Preliminary studies reported that high serum levels of G‐CSF or GM‐CSF may be useful for lung cancer diagnosis. 20 , 21 , 22 In the present study, increases in both myeloid cells and myeloid cell‐specific CSFs were detected using several types of cell subsets and CSFs. These findings indicate the important role of G‐CSF/GM‐CSF‐induced myeloid cell mobilization in the pathogenesis of lung cancer.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Third, we did not consider the medical conditions which were intrinsically linked to cancer recurrence and mortality, such as inflammatory bowel disease and concurrent malignancy. Fourth, we did not routinely measure inflammation-related markers (such as lymphocyte count and c-reactive protein) in this cohort and therefore could not adjust for them in the analyses 37 . Fifth, the follow-up period of this study is limited to August 2016.…”
Section: Discussionmentioning
confidence: 99%